How does "Modular hierarchical architecture concept" help us to enhance robot's function? - Mohsen, Taheri; S.H. Mohades, Kasaei; S.M. Mohades, Kasaei (Universiti Malaysia Perlis, 2009)
Organized by School of Mechatronic Engineering (UniMAP) & co-organized by The Institution of Engineering Malaysia (IEM), 11th - 13th October 2009 at Batu Feringhi, Penang, Malaysia.